Pengetahuan, Sikap, dan Fasilitas Pendukung terhadap Praktik Kebersihan Menstruasi Remaja Putri SMA Negeri 1 Kupang - Fransina Ndaong; Christina Rony Nayoan; Tanti Rahayu (Yayasan Literasi Sains Indonesia, 2026)
Menstrual hygiene is a significant public health issue influenced by multiple factors, knowledge, attitudes, and the availability of facilities. This study sought to examine the association between knowledge, attitudes, facilities, and menstrual hygiene practices among female students at SMA Negeri 1 Kupang. A quantitative analytic approach with a cross-sectional design was employed, involving 649 students as the population. Eighty-four respondents were chosen through proportional stratified random sampling. Data gathering was performed using structured questionnaires and observation checklists, followed by analysis using univariate and bivariate methods. The Chi-square test at a 5% significance level was applied to assess relationships between variables. Results showed that 50.0% of respondents had good knowledge about menstrual hygiene, 59.5% exhibited positive attitudes, and 75.0% demonstrated appropriate menstrual hygiene practices. Statistical analysis revealed a significant relationship between knowledge and menstrual hygiene practices (p < 0.001), as well as a significant association between attitudes and menstrual hygiene practices. Observations indicated that school facilities were moderately adequate, with six out of eight assessed indicators present. However, these facilities did not fully meet the standards required to optimally support menstrual hygiene management among students. Overall, the findings indicate that both knowledge and attitudes significantly influence menstrual hygiene practices among adolescent girls. While some facilities are available, their adequacy remains insufficient to fully facilitate proper menstrual hygiene. It is therefore recommended to strengthen reproductive health education programs to enhance students' knowledge and promote positive attitudes, alongside efforts to improve and optimize school facilities that support menstrual hygiene management.